Research on Time Synchronization Algorithm Based on Co-band Signal - Zhongliang, Deng; Wei, Shi; Gan, Wang; Lu, Yin (Proceedings of ... IEEE International Conference on Computer and Communications (Online), 2023)
In recent years, the Internet of Things (IoT) has imposed increasingly stringent requirements on time synchronization technology. While striving for continuous improvement in time synchronization accuracy, there is a simultaneous needed to minimize communication costs, leading to the emergence of various time synchronization protocols. TC-OFDM Co-band signal system has been used in IoT for years. In this paper, we propose a two-way mechanism and an Accumulation Timing Measure (ATM) algorithm based on the TC-OFDM Co-band signal system to reduce clock drift and costs of communication. The ATM aggregates N round-trip time (RTT) measurement results to derive a concise set of Accumulated Time measurement parameters, specifically estimating logical clock drift and logical clock offset, which facilitate complete information exchange for clock difference settlement. Through extensive simulations, we have observed that the ATM algorithm achieves nanosecond-level accuracy. Furthermore, we have found that the accuracy of ATM remains within 0.05 of the TPSN while substantially reducing communication costs with an increase in the number of communication cycles.